MYOCARDIAL INFARCTION AND THE ISSUE OF INDIVIDUALIZED MANAGEMENT. CLINICAL CASE OF SPONTANEOUS DISSECTION IN TWO CORONARY ARTERIES - M. N. Arefiev; L. L. Klykov; V. V. Krylov; V. A. Rusina; E. O. Taratukhin (Кардиоваскулярная терапия и профилактика)
The article is focused on the problem of evidence-based and individual approach relations in patient management, especially if a patient is on the periphery of statistical ranges. Recent literary data analyzed, on the opportunities for management individualization. Clinical case is provided of young female patient with spontaneous dissections of coronary arteries and myocardial infarction development.